2005
DOI: 10.1007/s10815-005-4923-5
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-1 and insulin-like growth factor binding protein-1 and 3 in the follicular fluid of infertile patients submitted to in vitro fertilization

Abstract: Purpose : In the present article we propose to evaluate IGF-1, IGFBP-1 and 3 in the follicular fluid of infertile patients submitted to in vitro fertilization. Methods : We performed a case-control study with 53 infertile patients submitted to the first in vitro fertilization attempt. We compared their follicular fluid concentration of IGF-1, IGFBP-1 and IGFBP-3 between the patients who became pregnant (n = 11) versus those nonpregnant (n = 42). Results : The clinical characteristics of patients from the two g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Cunha Filhos et al reported that IVF was more successful in patients with a low level of IGFBP-3 in the follicular fluid, and there was no correlation between IGF 1 and pregnancy [16]. According to another report by Dorn et al, there was a meaningful relationship between serum IGF 1, IGFBP 3 levels and pregnancy and no correlation between follicular IGF 1, IGFBP 3 and pregnancy [17].…”
Section: Discussionmentioning
confidence: 99%
“…Cunha Filhos et al reported that IVF was more successful in patients with a low level of IGFBP-3 in the follicular fluid, and there was no correlation between IGF 1 and pregnancy [16]. According to another report by Dorn et al, there was a meaningful relationship between serum IGF 1, IGFBP 3 levels and pregnancy and no correlation between follicular IGF 1, IGFBP 3 and pregnancy [17].…”
Section: Discussionmentioning
confidence: 99%
“…88 Recently, 3 clinical prospective studies investigated the intrafollicular concentrations of cytokines in patients stimulated with GnRH antagonist protocols. Cunha-Filho et al 103 investigated the intrafollicular concentrations of vascular endothelial growth factor (VEGF) and inhibin-A in patients minimally stimulated with a GnRH antagonist protocol for IVF and patients who underwent natural cycle IVF. Inhibin-A concentrations were similar between the 2 groups.VEGF concentrations were lower in patients treated with GnRH antagonist but not significantly different from the unstimulated patients.…”
Section: Direct Effects Of Gnrh Analogues On Ovarian Functionsmentioning
confidence: 99%